A Family Imprinting Approach to Nurturing Willing Successors: Evidence From Centennial Family Firms. (September 2022) - Marques, Pilar; Bikfalvi, Andrea; Busquet, Francesc
A critical aspect for the continuity of family businesses (FB) is the existence of willing successors. In this article, we use the imprinting theory to ground an explanation of how the family imprinting process shapes siblings' willingness to become a successor in the FB. We stylize three family imprinting types based mainly on different family motivations: the FB-centric, the entrepreneurship-centric, and the free-will-centric. The uniqueness of this approach is that it offers an imprinting-based process model capable of explaining the origins of homogeneity and heterogeneity in succession willingness at both the inter- and the intra-family levels.